2021
DOI: 10.5812/jjm.108540
|View full text |Cite
|
Sign up to set email alerts
|

Improved Visual Detection of speB Gene in Streptococcus pyogenes Isolates by Real-time Loop-Mediated Isothermal Amplification Turbidimetry Method

Abstract: Background: Group A Streptococcus (GAS) causes a wide array of clinical manifestations ranging from mild pharyngitis to suppurative and non-suppurative severe debilitating diseases. Hence, a simple, rapid detection method with high sensitivity and specificity is needed. Objectives: This study embarked on the visual detection of the streptococcal pyrogenic exotoxin B (speB) gene by Real-time Turbidimetry and Loop-mediated Isothermal Amplification (RT-LAMP) methods. The real-time monitoring of the sigmoidal grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It is already known that LAMP design is performed by using the S. pyogenes speB gene and is used in clinical samples for rapid diagnosis [ 2 , 25 , 26 ]. In their study, Cao et al reported that the sensitivity was 71.21% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that LAMP design is performed by using the S. pyogenes speB gene and is used in clinical samples for rapid diagnosis [ 2 , 25 , 26 ]. In their study, Cao et al reported that the sensitivity was 71.21% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%